UJI AKTIVITAS ANTIOKSIDAN FRAKSI n-HEKSAN, ETIL ASETAT, DAN AIR EKSTRAK DAUN BIWA (Eriobotrya japonica (Thunb.) Lindl.) DENGAN METODE DPPH - Kristi Melsi; Vivin Nopiyanti; Endang Sri Rejeki (As-Syifaa Jurnal Farmasi, 2022)
Loquat leaf (Eriobotrya japonica (Thunb.) Lindl.)  have been known to contain flavonoid compounds, alkaloids, tannins, saponins, triterpenoids and glycosides, these compounds have the potential to be antioxidants and can ward off free radicals. The purpose of this study was to determine the fraction of n-hexane ethyl acetate and water with extract of loquat leaf which have antioxidant activity, and to find out, respectively, which fraction had the most active activity from the IC50 value in activity antioxidant. The extraction method of loquat was macerated using 96% ethanol and then fractionated with n-hexane, ethyl acetate, and water. The obtained fraction was tested for antioxidant activity against free radicals using the DPPH method using UV-Vis spectrophotometer at the wavelength of 516 nm. The results of the loquat leaf fraction test have antioxidant activity which can be seen from the IC50 value, namely the n-hexane fraction is 1792 ppm, the ethyl acetate fraction is 89.60 ppm, the water fraction is 394.99 ppm, and quercetin is 13.03 ppm, so the most active antioxidant is obtained ethyl acetate